Nebulized Hypertonic Saline Treatment Reduces Both Rate and Duration of Hospitalization for Acute Bronchiolitis in Infants: An Updated Meta-analysis - Yen-Ju Chen; Wen-Li Lee; Chuang-Ming Wang; Hsin-Hsu Chou (Elsevier, 2014)
Nebulized hypertonic saline (HS) treatment reduced the length of hospitalization in infants with acute bronchiolitis in a previous meta-analysis. However, there was no reduction in the admission rate. We hypothesized that nebulized HS treatment might significantly decrease both the duration and the rate of hospitalization if more randomized controlled trials (RCTs) were included. We searched MEDLINE, PubMed, CINAHL, and the Cochrane Central Register of Controlled Trials (CENTRAL) without a language restriction. A meta-analysis was performed based on the efficacy of nebulized HS treatment in infants with acute bronchiolitis. We used weighted mean difference (WMD) and risk ratio as effect size metrics. Eleven studies were identified that enrolled 1070 infants. Nebulized HS treatment significantly decreased the duration and rate of hospitalization compared with nebulized normal saline (NS) [duration of hospitalization: WMD = −0.96, 95% confidence interval (CI) = −1.38 to −0.54, p < 0.001; rate of hospitalization: risk ratio = 0.59, 95% CI = 0.37-0.93, p = 0.02]. Furthermore, nebulized HS treatment had a beneficial effect in reducing the clinical severity (CS) score of acute bronchiolitis infants post-treatment (Day 1: WMD = −0.77, 95% CI = −1.30 to −0.24, p = 0.005; Day 2: WMD = −0.85, 95% CI = −1.30 to −0.39, p < 0.001; Day 3: WMD = −1.14, 95% CI = −1.69 to −0.58, p < 0.001). There was no decrease in the rate of readmission (risk ratio = 1.08, 95% CI = 0.68-1.73, p = 0.74). Nebulized HS treatment significantly decreased both the rate and the duration of hospitalization. Due to the efficacy and cost-effectiveness, HS should be considered for the treatment of acute bronchiolitis in infants.